Analysis of AVO and Seismic Inversion for Reservoir Characterization (Case Study: EP Field, South Sumatera Basin) - H Budiman; M. Y. N. Khakim; A. K. Afandi (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
A research about reservoir characterization with analysis of AVO (Amplitude Variation with Offset) and seismic inversion, to extract the petrophysics properties on the EP field South Sumatra Basin. This research was conducted to identify rock lithology and its spread, to see the sensitive parameters of physical properties of rocks. This research uses the 3D seismic data PSTM (Pre Stack Time Migration) as input control with data from the EP-036 well containing sonic log, density, gamma rays, neutron and resistivity log. From the results of data analysis on the well log chart EP-036, reservoir target zones are at a depth of 714 to 722 m (TVD) or time domain 768 to 780 ms. The results of the analysis AVO is able to detect the presence of reservoir gas sand, based on the classification of Rutherford and Williams (1989) the gas sand layer into AVO class III that indicates low impedance contrast sands. To analyze the results of well log data in the cross plot EP-036 indicates lithology is a hydrocarbon. It is also reinforced with cross plot analysis and seismic inversion results in the form of the parameter value ??, Vp/Vs and Acoustic impedance with low porosity averaging 22 to 35%, indicating that the zone is a zone reservoir potential gas sand. Keywords: Inversion, AVO, LMR, Reservoir Characterization.